An Exploratory Study Investigating Paediatric and Adult Healthcare Professionals’ Experiences relating to Transition of Young People from Child to Adult-centred Renal Transplant Services - Brown, April (2011)
Objectives: To explore the experiences of paediatric and adult renal transplant teams of transition. This study aims to create an exhaustive description of transition and identify the perceived role of both paediatric and adult health professionals. Background: Transition continues to be an important issue within the UK. However, there is a dearth of literature addressing the transition of renal patients. With risk of loss of transplants due to non-compliance (Watson, 2000), it is important that the transition of this group is continually addressed. Methods: This study used Husserl’s phenomenology methodology. Participants took part in one-on-one interviews, using a semi-structured technique. Interviews were recorded and then transcribed verbatim. Significant statements were extracted from the transcripts, and formulated into meaning. These meanings were then used to construct an exhaustive description of the phenomenon (transition). Results: 8 paediatric and 2 adult renal health professionals took part. Three themes were identified: Current Renal Transition Practice, Future Recommendations, and Barriers and Problems in Transition. Unique ways of preparing young people for transition were recognised, such as residentials and the use of transition packs. Non-compliance was experienced more by adult health professionals than paediatric health professionals. It was clear that paediatric health professionals play a significant role in the preparation of young people, however, adult health professionals only seemed to feature in the transition clinic, when the young people leave the paediatric service. Conclusion: This study illustrates that good transition preparation takes place in this unit, and therefore transition practice seems to be of a high standard in this centre. However, there are still areas of improvement. It would seem that non-compliance in still experienced by adult staff members, therefore, structures need to be put in place to avoid this. It was felt that conferences can help improve transition in the future.